Green, simple and convenient method for measuring lignin content in corn straw

Through the method of ethanol extraction and 7% NaOH/12% urea solution standing treatment, the complexity and inaccuracy of lignin content determination in corn stalks were solved, and simple and accurate lignin content determination was achieved.

CN119470312APending Publication Date: 2025-02-18NANJING UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411377015.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, when determining the lignin content in corn stalks, there are problems such as large sample volume, complex operation, damage to lignin structure and interference with the introduction of substances, resulting in inaccurate measurement results.

Method used

After Soxhlet extraction was performed using ethanol, the corn straw powder was left to stand with 7% NaOH/12% urea solution, and the concentration of lignin was obtained by ultraviolet absorbance, and a standard curve was established to calculate the lignin content.

Benefits of technology

This method simplifies the pretreatment steps, is more convenient to operate, avoids the use of sulfuric acid, provides more accurate lignin content measurement results, and is suitable for a wide range of corn stalk samples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470312A_ABST
    Figure CN119470312A_ABST
Patent Text Reader

Abstract

The invention discloses a green, simple and convenient method for measuring the content of lignin in corn straw. The lignin content determination method is innovated by the following steps: firstly, pulverizing corn straws, and then degreasing and drying a to-be-determined sample by using ethanol. And adding the pretreated corn straw powder into urea, and standing and storing at 25 DEG C. And then absorbing the dissolved solution for centrifugation, measuring the absorbance of the supernate obtained by centrifugation at 298nm, and substituting the absorbance into a standard curve and a formula to calculate the lignin content. The method disclosed by the invention has the characteristics of simplicity and convenience in operation, few steps, environmental friendliness and wide applicability, the absorbance measurement is reduced into the 96-well plate, the sample dosage is reduced, and an accurate measurement result can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resources and environment, and in particular relates to a green and simple method for determining the lignin content in corn stalks. Background Art

[0002] Crop straw is an important biomass resource. According to the 2022 FAO statistical yearbook, since 2000, the output of major crops such as sugarcane, corn, wheat and rice has increased by 52% from 2000 to 2020, reaching 9.3 billion tons. China, as the country with the largest corn planting area in the world, ranks second in the world in corn production, with an annual output of 260 million tons, accounting for about 23% of the world's production. In 2021, the national straw production was 865 million tons, of which corn straw production reached 321 million tons, accounting for 37%. Compared with other crop straws, corn straw has the characteristics of high carbon-nitrogen ratio, high hardness, high cellulose, and high calorific value, which makes it have high utilization value in fertilizer, fuel, feed, raw material and base material. The quantitative determination of lignin is the prerequisite for the characterization, conversion and utilization of lignocellulosic biomass. At present, Klason is mostly used to determine the lignin content in corn straw, but in practical applications, the required sample volume is large and the operation is complicated.

[0003] Currently, the Claessen method is the most widely used direct quantitative method for lignin, but the measurement process often involves problems such as large sample volume, destruction of lignin structure, changes in lignin quantity, and introduction of interfering substances, which affect the lignin content determination results.

[0004] Chinese patent CN201310228172 discloses a method for determining the content of lignin in tobacco, in which sodium hydroxide / urea solution is also used, but it uses sodium hydroxide / urea solution to dissolve "cellulose and hemicellulose in tobacco" and removes "water-soluble sugars, proteins and other free impurities in tobacco", rather than lignin. In this method, lignin is divided into two parts, one part is acid-soluble lignin, and the content of this part of lignin is determined by ultraviolet; the other part is acid-insoluble lignin, and the content of this part of lignin is determined by weighing. Chinese patent CN202210680840 discloses a method for determining the content of lignin in tobacco stems, in which the tobacco stem filter residue containing fat-soluble substances, pigments, soluble sugars and phenolic substances, starch, cellulose, pectin and protein is first removed. Then the tobacco stem filter residue is treated with NaOH / urea solution to obtain a filter residue rich in lignin. The obtained filter residue is then subjected to acid hydrolysis with a sulfuric acid solution to obtain acid-soluble lignin (supernatant) and crude acid-insoluble lignin (lower filter residue). The acid-soluble lignin content is measured by a spectrophotometer, and then the crude acid-insoluble lignin (lower filter residue) is treated again with a NaOH / urea solution to remove cellulose and hemicellulose. The remaining solid component is the acid-insoluble lignin, and the content is calculated. However, since sodium hydroxide solution or sodium hydroxide / urea solution will dissolve lignin, the measured lignin content is lower than the true value of the sample, so these two methods are actually difficult to achieve the purpose of accurately measuring the lignin content. Summary of the invention

[0005] The purpose of the present invention is to establish a relatively green, convenient, rapid, extensive and stable method for determining the lignin content in corn stalks based on the existing technology and the research results of predecessors by analyzing the relationship between the lignin content and UV absorption in a specific lignin solution.

[0006] The purpose of the present invention can be achieved by the following measures:

[0007] A green and simple method for determining the lignin content in corn stalks comprises the following steps:

[0008] Step A, crushing corn stalks;

[0009] Step B, performing Soxhlet extraction on the corn stalk powder using ethanol, and then drying the corn stalk powder;

[0010] Step C, taking dried corn stalk powder, adding it into a NaOH / urea solution and letting it stand to obtain a test solution;

[0011] Step D, centrifuging the test solution and measuring the ultraviolet absorbance of the obtained supernatant at 298 nm;

[0012] Step E, bringing the measured ultraviolet absorbance value into the standard curve to obtain the concentration C (%) of lignin in the test solution, and calculating the mass content of lignin in the corn stalk; the standard curve is:

[0013] Abs=10.262C+0.0811

[0014] Where: Abs is the UV absorbance value; C is the concentration of lignin in the test solution, in mg / mL.

[0015] In a preferred embodiment, in step A, the corn stalks are crushed and then passed through a 40-mesh sieve.

[0016] In a preferred embodiment, in step B, the ethanol is 90% to 98% ethanol, preferably 95% ethanol; the solid-liquid ratio during the extraction process is 1:15 to 25, preferably 1:20; the extraction is carried out until the liquid in the reflux tube is colorless, and then the corn stalk powder is placed in an oven for drying.

[0017] Step A of the present application is a powdering treatment, and step B is a defatting treatment, wherein powdering and defatting are pretreatment methods for the determination of lignin content, powdering is conducive to obtaining a uniform sample and increasing the contact area between the sample and the reagent, and defatting is conducive to eliminating other interferences and facilitating the determination of acid-soluble lignin or lignin absorbance. In the method of the present application, only two pretreatment steps of powdering and defatting are required, which is simple to operate and does not affect the accuracy of the determination of lignin content.

[0018] In a preferred embodiment, in step C, the NaOH / urea solution is an aqueous solution containing 5-12 wt% NaOH and 8-20 wt% urea, preferably a 7% NaOH / 12% urea solution. We found that using a 7% NaOH / 12% urea solution can obtain a more accurate lignin content determination result compared with using a NaOH / urea solution of other concentrations, while using other concentrations will produce more or less errors.

[0019] In a preferred embodiment, in step C, the ratio of corn stalk powder to NaOH / urea solution is 1:1-3 mg / mL, preferably 1:2 mg / mL, and the standing time is 15-30 h, preferably 24 h. The standing temperature is 20-30 ° C, preferably 25 ° C. We found that the lignin content measurement result obtained by standing and storing corn stalks at 25 ° C using the method of the present invention is close to that using the existing Klason method, and the result is more accurate and significantly better than other reaction temperatures.

[0020] The present invention particularly establishes a relatively green, convenient, rapid, extensive and stable method for determining the lignin content in corn stalks by analyzing the relationship between the lignin content and UV absorption in 7% NaOH / 12% urea, wherein the lignin solution can be prepared according to the mass ratio of NaOH: urea: water = 7:12:81.

[0021] In a preferred embodiment, in step C, 2 mg of corn stalk powder is accurately weighed and placed in a 4 mL glass vial, and 4.0 mL of 7% NaOH / 12% urea lignin solution is added, and the mixture is stored at 25° C. for 24 h.

[0022] In a preferred embodiment, in step D, the centrifugal speed is 8000-12000 rpm, preferably 10000 rpm; the centrifugal time is 1-5 min, preferably 3 min.

[0023] In a preferred embodiment, in step D, 400 μL of the test solution is placed in a centrifuge tube and centrifuged at 10,000 rpm for 3 min; 200 μL of the supernatant obtained by centrifugation is taken and placed in a 96-well plate without UV absorption, and the absorbance is measured at 298 nm.

[0024] In a preferred embodiment, in step E, the measured ultraviolet absorbance value is substituted into the standard curve for lignin content determination to calculate the lignin concentration in the solution, and then the lignin concentration is substituted into the calculation formula for corn straw lignin content:

[0025]

[0026] C: the concentration of lignin in the test solution, unit: mg / mL;

[0027] B: dilution multiple;

[0028] m: the weight of the pretreated corn straw powder, unit: mg;

[0029] x: lignin mass content of corn straw.

[0030] In a preferred embodiment, the method of the present invention comprises the following steps:

[0031] Step 1: grind the corn stalks to be tested into powder and pass through a 40-mesh sieve;

[0032] Step 2: Degreasing the corn stalk powder by Soxhlet extraction with 95% ethanol, and then drying it in an oven;

[0033] Step 3, preparing 7% NaOH / 12% urea lignin solution;

[0034] Step 4: accurately weigh 2 mg of pretreated corn stalk powder, add 4 mL of NaOH / urea solution, and store at 25°C for 24 h;

[0035] Step 5, aspirate the test solution, place it in a centrifuge tube, centrifuge, take the supernatant, place it in a 96-well plate, and measure the ultraviolet absorbance at 298 nm;

[0036] Step 6: Substitute the ultraviolet absorbance value measured in step 4 into the following standard curve to calculate the concentration and content of lignin in corn stalks; the standard curve is:

[0037] Abs=10.262C+0.0811

[0038] Where: Abs is the UV absorbance value; C is the concentration of lignin in the test solution, unit: mg / mL.

[0039] Preferably, according to steps one and two, the corn stalk sample to be tested is defatted using 95% ethanol at a solid-liquid ratio of 1:20 until the liquid in the reflux pipe is colorless, and then placed in an oven for drying.

[0040] Preferably, according to steps three and four, 2 mg of pretreated corn stalk powder is accurately weighed (weighed to an accuracy of 0.01 mg), placed in a 4 mL glass vial, and 4.0 mL of 7% NaOH / 12% urea lignin solution is added, and stored at 25° C. for 24 h.

[0041] Preferably, according to step 5, 400 μL of the solution is placed in a centrifuge tube and centrifuged at 10,000 rpm for 3 min. 200 μL of the supernatant obtained by centrifugation is taken and placed in a 96-well plate without UV absorption, and the absorbance is measured at 298 nm.

[0042] Preferably, as described in step 6, the absorbance measured in step 5 is substituted into the standard curve of lignin content determination to calculate the lignin concentration in the solution. Finally, the lignin concentration is substituted into the calculation formula of corn straw lignin content:

[0043]

[0044] C: lignin concentration in the test solution, unit: mg / mL;

[0045] B: dilution multiple;

[0046] m: the weight of the pretreated corn straw powder, unit: mg;

[0047] x: lignin mass content of corn straw.

[0048] In a specific embodiment, the lignin standard used in the standard curve in step 6 is a lignin standard purchased from SigmaAldrich, with a serial number of 471003.

[0049] The beneficial effects of the present invention are as follows: compared with the prior art, the present invention does not need to introduce sulfuric acid during the pretreatment and determination process, nor does it need to distinguish between acid-soluble lignin and acid-insoluble lignin. The lignin content determination operation is simpler and does not require the step-by-step determination operation of the weighing method combined with the ultraviolet method in the conventional lignin content determination method. Moreover, the reaction process adopted in the present invention is a method of standing at room temperature (25°C), which does not require other operations and is simpler.

[0050] The present invention has the characteristics of simple operation, few steps, environmental friendliness and wide applicability, and can reduce the absorbance measurement to a 96-well plate, reduce the sample dosage, and provide accurate measurement results. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 It is the full wavelength scanning result of the lignin standard in the present invention in 7% NaOH / 12% urea solution;

[0052] Figure 2 It is the standard curve of lignin in 7% NaOH / 12% urea solution in the present invention;

[0053] Figure 3 It is the content determination result of lignin in NaOH / urea solution of different concentrations in the present invention;

[0054] Figure 4 It is the content determination result of lignin in 7% NaOH / 12% urea solution at different temperatures in the present invention. DETAILED DESCRIPTION

[0055] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0056] The present invention is further described in conjunction with specific examples. The following examples are only for explaining the present invention and are not intended to limit the content thereof. If the specific experimental conditions are not specified in the examples, they are usually carried out according to conventional conditions or the conditions recommended by the reagent company; the reagents and consumables used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0057] The present invention will be further described below in conjunction with specific embodiments and accompanying drawings, and the advantages and features of the present invention will become clearer as the description proceeds. However, the embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.

[0058] Example 1

[0059] 1. Grind the corn stalks to be tested into powder and pass through a 40-mesh sieve.

[0060] 2. The corn stalk powder was degreased by Soxhlet extraction with 95% ethanol, and the extraction was performed at a solid-liquid ratio of 1g:20mL until the liquid in the reflux tube was colorless, and then placed in an oven for drying.

[0061] 3. Prepare lignin solution according to the mass ratio of NaOH: urea: water (7:12:81).

[0062] 4. Standard curve for lignin content determination: Accurately weigh the lignin standard, dissolve it in 7% NaOH / 12% urea solution to prepare a solution with a concentration gradient of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, and 0.10 mg / mL, and draw 200 μL into a 96-well plate without UV absorption for full wavelength scanning.

[0063] The scan results are as follows Figure 1 As shown, it was found that the lignin standard had characteristic absorption at 298nm, and a standard curve was established (such as Figure 2 As shown), the linear relationship is good, R 2 =0.9993.

[0064] 5. Determination of lignin content in corn straw: Accurately weigh 2 mg of pretreated corn straw powder (weighing to an accuracy of 0.01 mg), place it in a 4 mL glass vial, and add 4.0 mL of 7% NaOH / 12% urea lignin solution, seal the mixture, and store it at 25°C for 24 hours. Take 400 μL of the liquid in the solution and place it in a centrifuge tube, and centrifuge it at 10,000 rpm for 3 minutes. Take 200 μL of the supernatant obtained by centrifugation, place it in a 96-well plate without UV absorption, and measure the absorbance at 298 nm. The measured absorbance is substituted into the lignin content determination standard curve to calculate the lignin concentration in the solution. Finally, substitute the concentration into the calculation formula for the lignin content in corn straw:

[0065]

[0066] C: the concentration of lignin in the test solution, unit: mg / mL;

[0067] B: dilution multiple;

[0068] m: the weight of the pretreated corn straw powder, unit: mg;

[0069] x: lignin mass content of corn straw.

[0070] 6. The results of the lignin content determination of corn straw are shown in the following table:

[0071] Table 1 Determination results of lignin content in corn straw

[0072]

[0073] Example 2

[0074] 1. Grind the corn stalks to be tested into powder and pass through a 40-mesh sieve.

[0075] 2. The corn stalk powder was degreased by Soxhlet extraction with 95% ethanol, and the extraction was performed at a solid-liquid ratio of 1g:20mL until the liquid in the reflux tube was colorless, and then placed in an oven for drying.

[0076] 3. Prepare lignin solutions with different concentrations of NaOH:urea:water in mass ratios of 6.5:15:78.5, 12:8.5:79.5, 7:12:81, 10.5:20:69.5, 5:8:87, and 8:15:77.

[0077] 4. Standard curve for lignin content determination: Weigh the lignin standard accurately and dissolve it in NaOH / urea solution. Prepare a solution with a concentration gradient of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10 mg / mL. Pipette 200 μL and add it to a 96-well plate without UV absorption for full wavelength scanning. The scanning results are as follows: Figure 1 shown.

[0078] 5. Determination of lignin content in corn straw: Accurately weigh 2 mg of pretreated corn straw powder (weighing to an accuracy of 0.01 mg), place it in a 4 mL glass vial, and add 4.0 mL of NaOH / urea lignin solution, seal the mixture, and store it at 25°C for 24 hours. Take 400 μL of the liquid in the solution and place it in a centrifuge tube, and centrifuge it at 10,000 rpm for 3 minutes. Take 200 μL of the supernatant obtained by centrifugation, place it in a 96-well plate without UV absorption, and measure the absorbance at 298 nm. The measured absorbance is substituted into the lignin content determination standard curve to calculate the lignin concentration in the solution. Finally, substitute the concentration into the calculation formula for the lignin content of corn straw:

[0079]

[0080] C: the concentration of lignin in the test solution, unit: mg / mL;

[0081] B: dilution multiple;

[0082] m: the weight of the pretreated corn straw powder, unit: mg.

[0083] x: lignin mass content of corn straw.

[0084] 6. NaOH / urea concentration in corn straw lignin content determination: By comparing different NaOH / urea ratios, the results are as follows Figure 3 As shown, it was found that the lignin content of corn straw in 7% NaOH / 12% urea was close to Klason, and the result was more accurate and significantly better than other alkali solution concentration ratios.

[0085] 7. Reaction temperature for determination of lignin content in corn straw: By comparing the determination of lignin content in 7% NaOH / 12% urea at different temperatures, the results are as follows Figure 4 As shown, it was found that the lignin content determination results of corn stover at 25°C were close to Klason, and the results were more accurate and better than other reaction temperatures.

[0086] 8. From the above experimental results, it can be seen that the lignin content in corn straw was determined by using 7% NaOH / 12% urea at 25°C according to a 2mg-4mL solid-liquid ratio. The experimental result was 18.77%, which is close to the 18.94% determined by the Klason method.

[0087] The present invention is committed to developing a method for determining lignin content that is simple to operate, has fewer steps, is environmentally friendly, and has wide applicability, and reduces the absorbance determination to a 96-well plate, thereby reducing the sample dosage and providing accurate determination results.

[0088] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the experimental conditions without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0089] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

Claims

1. A green and simple method for determining the lignin content in corn stalks, characterized in that The following steps are involved: Step A, crushing corn stalks; Step B, performing Soxhlet extraction on the corn stalk powder using ethanol, and then drying the corn stalk powder; Step C, taking dried corn stalk powder, adding it into a NaOH / urea solution and letting it stand to obtain a test solution; Step D, centrifuging the test solution and measuring the ultraviolet absorbance of the obtained supernatant at 298 nm; Step E, bringing the measured ultraviolet absorbance value into the standard curve to obtain the concentration C (%) of lignin in the test solution, and calculating the mass content of lignin in the corn stalk; the standard curve is: Abs=10.262C+0.0811 Where: Abs is the UV absorbance value; C is the concentration of lignin in the test solution, unit: mg / mL.

2. The method according to claim 1, characterized in that In step A, the corn stalks are crushed and then passed through a 40-mesh sieve.

3. The method according to claim 1, characterized in that In step B, the ethanol is 90% to 98% ethanol, preferably 95% ethanol; the solid-liquid ratio during the extraction process is 1:15 to 25, preferably 1:20; the extraction is performed until the liquid in the reflux tube is colorless, and then the corn stalk powder is placed in an oven for drying.

4. The method according to claim 1, characterized in that In step C, the NaOH / urea solution is an aqueous solution containing 5-12wt% NaOH and 8-20wt% urea, preferably 7% NaOH / 12% urea solution; the usage ratio of corn straw powder to NaOH / urea solution is 1:1-3mg / mL, preferably 1:2mg / mL, the standing time is 15-30h, preferably 24h, and the standing temperature is 20-30°C, preferably 25°C.

5. The method according to claim 4, characterized in that In step C, 2 mg of corn straw powder was accurately weighed and placed in a 4 mL glass vial, and 4.0 mL of 7% NaOH / 12% urea lignin solution was added, and the mixture was stored at 25° C. for 24 h.

6. The method according to claim 1, characterized in that In step D, the centrifugal speed is 8000-12000 rpm, preferably 10000 rpm; the centrifugal time is 1-5 min, preferably 3 min.

7. The method according to claim 1, characterized in that In step D, 400 μL of the test solution was placed in a centrifuge tube and centrifuged at 10,000 rpm for 3 min. 200 μL of the supernatant obtained by centrifugation was taken and placed in a 96-well plate without UV absorption, and the absorbance was measured at 298 nm.

8. The method according to claim 1, characterized in that In step E, the measured ultraviolet absorbance value is substituted into the standard curve for lignin content determination to calculate the lignin concentration in the solution, and then the lignin concentration is substituted into the calculation formula for the lignin content of corn straw: C: lignin concentration in the test solution, unit: mg / mL; B: dilution multiple; m: the weight of the pretreated corn straw powder, unit: mg; x: lignin mass content of corn straw.

9. The method according to claim 1, characterized in that The following steps are involved: Step 1: grind the corn stalks to be tested into powder and pass through a 40-mesh sieve; Step 2: Degreasing the corn stalk powder by Soxhlet extraction with 95% ethanol, and then drying it in an oven; Step 3, preparing 7% NaOH / 12% urea lignin solution; Step 4: accurately weigh 2 mg of pretreated corn stalk powder, add 4 mL of NaOH / urea solution, and store at 25°C for 24 h; Step 5, aspirate the test solution, place it in a centrifuge tube, centrifuge, take the supernatant, place it in a 96-well plate, and measure the ultraviolet absorbance at 298 nm; Step 6: Substitute the ultraviolet absorbance value measured in step 4 into the following standard curve to calculate the concentration and content of lignin in corn stalks; the standard curve is: Abs=10.262C+0.0811 Where: Abs is the UV absorbance value; C is the concentration of lignin in the test solution, unit: mg / mL.

10. The method according to claim 9, characterized in that In step six, the measured UV absorbance value is substituted into the standard curve for lignin content determination to calculate the lignin concentration in the solution, and then the lignin concentration is substituted into the calculation formula for corn straw lignin content: C: lignin concentration in the test solution, unit: mg / mL; B: dilution multiple; m: the weight of the pretreated corn straw powder, unit: mg; x: lignin mass content of corn straw.

Citation Information

Patent Citations

  • Measuring method of content of lignin in tobacco

    CN103335974A

  • Method for determining content of lignin in tobacco stems

    CN114964972A